Assessing young children’s musical enculturation: a novel method for testing sensitivity to key membership, harmony, and musical metre - Einarson, Kathleen M.; Corrigall, Kathleen; Trainor, Laurel J. (My University, 2012)
Western adults with no formal music training have implicit knowledge of the tonal and metrical structure of music within their culture (Hannon & Trehub, 2005; Tillmann, Bharucha, & Bigand, 2000; Trainor & Trehub, 1992), but little research has explored the developmental trajectory of these abilities. Here we test Western preschool children's knowledge of Western key membership and harmony. We also test their ability to perceive simple metrical structures typical of Western music and to complex meters common in some foreign, but not Western, musical systems (London, 1995).
Keywords: development; enculturation; harmony perception; metric processing; rhythm